Consequences of Mesobuthus tamulus gangeticus (Pocock, 1900) envenomation in albino mice - Chaubey,MK (2010)
The present study aimed to investigate the effects of Mesobuthus tamulus gangeticus Pocock (Buthidae) venom on albino mice (NIH strain). Whole venom was obtained by electrical stimulation and its toxicity was determined in albino mice by subcutaneous envenomation. The venom LD50 was 2.5 mg kg-1 of mouse body weight. Toxic effects on different biochemical and enzymatic parameters in blood serum and other tissues of albino mice were determined after experimental envenomation with sublethal doses of M. tamulus gangeticus venom. Increased levels of glucose, uric acid and cholesterol, as well as decreased serum total proteins, were observed at 2 and 4 hours after the envenomation. In the liver and muscles, glycogen content dropped after venom injection. Moreover, M. tamulus gangeticus venom elevated the enzymatic activity of acid phosphatase (ACP), lactic dehydrogenase (LDH) and alanine aminotransferase (ALT) in the serum of albino mice. In conclusion, M. tamulus gangeticus can be considered a lethal scorpion species.